It’s Not Busy Work - Denison, Veronica; Coleman, Tara (My University, 2021)
In the wake of the COVID 19 pandemic at Kansas State University many library employees needed to be able to do work from home or risk the prospect of not getting paid. The university archivist and the web services librarian got together to develop digital projects that could be completed without any special equipment other than a computer and internet. These projects benefited the university archives by making history more accessible and visible to others. We will show the processes that were used, the final product, and feedback from a library employee who worked on these projects.
Keywords: COVID 19; Pandemic; Remote work; Web services; Libraries and archives; Digital projects